Academic anxiety and a micro-online intervention for enhancing psychological capital - Rambau, Karabo Fellicia (University of the Witwatersrand, Johannesburg, 2022)
This study investigates the effectiveness of a Psychological Capital (PsyCap) intervention in reducing students’ levels of academic anxiety. In essence, the current study focuses on academic anxiety with the aim of investigating whether a PsyCap intervention is able to reduce students’ perceptions of academic anxiety. Regarding this, the current study also aims to enhance students’ levels of PsyCap so that students can be able to cope with academic anxiety. This study also utilised the Conservation of Resources (CoR) model to frame the relationship between PsyCap and academic anxiety by arguing that the accumulation of personal resources (i.e., PsyCap) could act as a buffer and reduce the experience of academic anxiety among students. It is of paramount importance that students are equipped with the necessary resources or skills that are needed in order to survive and excel within higher education. This is because being a university student can come with countless challenges that are sometimes unbearable. Regarding this, Rehman (2016) have argued that students entering the higher education system often come across numerous issues such as, academic anxiety, academic stress, academic depression, as well as socio-economic hardships. The lack of research regarding enhancing students’ PsyCap in order to help them cope with academic anxiety has motivated the researcher to engage in this topic. In engaging in this topic, the current study adopted a positive psychology approach which focuses on individual’s strengths and capabilities. This study employed a quantitative quasi-experimental research design. Additionally, a non-probability, convenience sampling technique was utilised. Data was collected using a questionnaire, the questionnaire consisted of a self-developed demographic questionnaire, the Psychological Capital Questionnaire (PCQ) (Luthans, Avolio, Avey, & Norman, 2007; Luthans, Youssef, & Avolio, 2007), and the Academic Anxiety Scale (AAS) (Cassady, Pierson & Starling, 2019). The final sample (N=110) consisted of first year Psychology students from the University of the Witwatersrand, Johannesburg, in South Africa. Results of the current study confirm the effectiveness of the PsyCap intervention in enhancing students’ level of PsyCap. This implies that the intervention was effective in enhancing students’ PsyCap. Nonetheless, the intervention was not effective in reducing students’ levels of academic anxiety. The results of the current study also indicated that PsyCap and academic anxiety are related. In this case, a significant, negative relationship was found between PsyCap overall and academic anxiety, in Time 0, Time 1, and in Time 2. The results of the current study were discussed in relation to previous literature and previous research.
A research project submitted in partial fulfilment of the requirement for the degree of MA by Coursework and Research in the field of Industrial/Organisational Psychology, School of Human and Community Development, in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2022.
Keywords: Psychological Capital; Academic Anxiety; Conservation of Resources model; University students; PsyCap intervention; Quasi-experimental research design; UCTD; SDG-4: Quality education